DOMAIN STATE STABILIZATION BY ITERATED THERMAL MAGNETIZATION PROCESSES - Fabian K.; Shcherbakov V.P. (My University, 2004)
Repeated heating and cooling cycles appear frequently in thermomagnetic experiments used to infer the palaeomagnetic field intensity. According to the fundamental assumptions used to interpret these measurements, a remanence acquired at some temperature T is not influenced by subsequent heating and cooling cycles at lower temperatures. This presumption is tested for natural and synthetic multidomain particle ensembles in the case of the so-called tail of pTRM ∗ (partial thermoremanent magnetization). This case is of special interest, since hitherto no theoretical explanation for the tail of pTRM ∗ has been available. The experimental results for all samples show that repeating the acquisition process for the tail of pTRM ∗ leads to an asymptotic saturation. This phenomenon can be explained in terms of a statistical theory of multidomain thermoremanence based on concepts of non-equilibrium thermodynamics. The presented experiments support the hypothesis that domain state stabilization by iterated thermal magnetization processes in multidomain particle ensembles is a statistical process. Iterative saturation of the tail of pTRM ∗ can be interpreted using a combination of exponential saturation functions related to the subspectrum of the involved transition matrix. Its explanation does not require chemical alteration or irreversible after-effects.
Keywords: rock magnetism; stochastic matrix; thermoremanent magnetization